Escandalosos, ebrios, malos y pendencieros. Militares, milicianos y guardas que deshonran su institución, ciudad de México (1822-1860) - Ceja Andrade, Claudia (El Colegio de México, A.C., 2023)
This article’s objective is to analyze some of the bad practices of the men of the Mexico City security forces, both civil and military, during the first half of the nineteenth century. If these security forces were established to ensure order and public safety, something that was partially accomplished, it’s also true that their members were the authors of a wide variety of transgressions, public and private, which were denounced by society as a whole. Through a variety of primary and secondary sources, this article offers an understanding of certain ideas and values that show how these subjects were accustomed to relating to others through the use of force, violence, codes of honor and private arrangements above the law.